A Study on Nestle Promotion Strategy - Singh, Padmalini; Sin, Liem Gai; Binti Kama’Aziri, Nur Shafiqah; Jian, Oh Zi; Binti Mohd Azlan, Nur Amiera Sofea; Binti Ibrahim, Putri Nur Illya Balkhis; Sheng, Dave Hoo; Kee, Daisy Mui Hung; Heng, Joseph Tan Soo; Wee, Liew Siaw; Ying, Lim York (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
This study aims to identify the most effective promotional medium used by Nestle. Nestle is the most successful manufacture which processes high quality and nutrition food and beverage to the Malaysians. To inspire consumers to purchase their products, Nestle must transform their promotional strategies frequently. A research will be conducted to collect information from respondent based on different characteristics to identify which is the most effective promotional medium used by Nestle. Through this research, we establish that the most effective promotional medium is Buy 1 Get 1 under sales promotion that helps consumers save more money. We have applied the implication idea to Nestle that can satisfy the customers’ needs and achieve sales target.